Development of Discharge Planning for Stroke Patients - Rosadi, Muhammad Imron; Arofiati, Fitri (Folia Medica Indonesiana, 2023)
Highlights: 1. Given the frequent long-term complications of stroke, this study identified the ideal approach to discharge planning to improve the quality of life of patients and hospital care. 2. This study provides evidence supporting the effectiveness of a conventional discharge planning approach that incorporates specific educational intervention with interactive learning through audiovisual media. 3. The approaches presented in this study may offer valuable perspectives on enhancing health service provisions, particularly regarding the discharge planning process for nurses. Abstract The quality improvement of discharge planning is essential throughout the development of discharge planning, which guarantees a seamless transition of care for stroke patients and family preparedness. This systematic review aimed to analyze the development of discharge planning and its impact on stroke patients and their families. The research was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Eligible pieces of literature were compiled from seven electronic databases, i.e., ScienceDirect, Scopus, PubMed, EBSCOhost, ProQuest, SAGE Journals, and Google Scholar. The literature search was performed using predetermined search terms, with specific criteria that included papers exclusively published in English and studies conducted in 2018–2022. The development of discharge planning showed a significant impact on stroke patients, as it could influence various aspects of their quality of life. This included improvements in physiological function, enhanced cognitive knowledge, increased satisfaction and self-efficacy, reduced stress levels and care burden, and the opportunity for families to adequately prepare for home-based patient care. This study concluded that integrating conventional with technology-based media is effective for developing discharge plans for stroke patients. The implementation of this novel approach in a health system can improve patient outcomes, family preparedness when providing care, and the quality of hospital care.